Evaluation of Mandibular Third Molar Region in a Turkish Population Using Cone-Beam Computed Tomography - Orhan, Büyük K.; Yılmaz, Dilek; Ozemre, Mehmet Ozgur; Kamburoğlu, Kıvanç; Gulen, Orhan; Gulsahi, Ayse (Current Medical Imaging, 2020)
Objectives: To evaluate impacted mandibular third molar tooth region and obtain linear measurements using CBCT images and to assess the relationship between the impacted third molar and the mandibular canal. Methods: CBCT scans of 351 patients (208 females, 143 males) were assessed. Age, gender, and impaction site were recorded for each patient. The relationship of third molars with the vertical axis of second molars, 2nd molar resorption and the relationship between third molar apices and the mandibular canal were assessed. In addition, the distance between ramus and second molar, mesiodistal width of the third molar, the angle between third molar and second molar, and width of the third molar capsule were measured. Binary Logistic Regression, Chi-Square Test, and General Linear Model were used for statistical analysis. Results: The highest percentage of impaction was found for mesioangular followed by transversal and vertical. The transversal impacted third molars revealed a significant association with adjacent second molar root resorption (p<0.001). There was a statistical significance between the second molar resorption and distance between ramus and second molar (p<0.001). The mesioangular impacted third molars revealed significant relation with the mandibular canal (p<0.05). The most frequent variation found was the dental canal followed by the retromolar canal. In general, higher measurement values were obtained for men when compared to women (p<0.05). Conclusion: CBCT assessment of the third molar region provided useful information regarding impacted mandibular third molar surgery operations.
Keywords: patients